Assessment of physiological and electrochemical effects of a repurposed zinc dithiocarbamate complex on Acinetobacter baumannii biofilms - Yang, Qing; Olaifa, Kayode; Andrew, Fartisincha P.; Ajibade, Peter A.; Ajunwa, Obinna M.; Marsili, Enrico (Scientific reports, 2022)
Acinetobacter baumannii is an infectious agent of global proportion and concern, partly due to its proficiency in development of antibiotic resistance phenotypes and biofilm formation. Dithiocarbamates (DTC) have been identified as possible alternatives to the current antimicrobials. We report here the evaluation of several DTC-metal complexes against A. baumannii planktonic cells and biofilms. Among the DTC-metal complexes and DTCs tested, ZnL1 ( N -methyl-1-phenyldithiocarbamato-S,S′ Zn(II)), originally designed as an antitumor agent, is effective against biofilm forming A. baumannii. A MIC value of 12.5 µM, comparable to that of Gentamicin (5 µM) was measured for planktonic cells in tryptic soy broth. Spectroscopy, microscopy and biochemical analyses reveal cell membrane degradation and leakage after treatment with ZnL1. Bioelectrochemical analyses show that ZnL1 reduces biofilm formation and decreases extracellular respiration of pre-formed biofilms, as corroborated by microscopic analyses. Due to the affinity of Zn to cells and the metal chelating nature of L1 ligand, we hypothesize ZnL1 could alter metalloprotein functions in the membranes of A. baumannii cells, leading to altered redox balance. Results indicate that the DTC-Zn metal complex is an effective antimicrobial agent against early A. baumannii biofilms under laboratory conditions.